Derivational Affixes in Youtube Video Vsauce - Tiasyah Alifiah Rajabni Harahap (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Affixation is the most common process that is used by people and it is used because most of the new words created by using affix. The aims of this research were: 1) To find out the most dominant derivational affixes used in YouTube video Vsauce.; 2) To investigate the process of derivational affixes found in YouTube video Vsauce. This research used the descriptive qualitative method. The results of this research showed that the data about derivational affixes which used by the YouTube channel Vsauce, the researcher found that there were 165 derivational affixes found in 20 videos by YouTube channel Vsauce, and he also used all of the kinds of derivational affixes in his videos. The research reflected that the speaker wants to make a clarity for the viewers about the expression and explanation of his topic or the condition that happened in his video.Keywords: Morphology, Derivational, Affixation, Youtube.